Language Style in Opinion Pages of Three Popular Mass Media (Universitas Pamulang, 2024)
The language style is the way humans communicate with others through spoken and written. Human communicates with the language style that depends on the cultural ideology and the context of the situation. This study was aimed to find out the kind of language styles in three popular mass media. The data source of this study was selected from newspapers mainly on opinion pages. The method to analyze the study was descriptive qualitative. The instruments used to analyze the study were note-taking. To analyze the data source, the writer used the theory of Joos (1967) that discusses language style. The result of the analysis shows that the three newspaper articles use a different type of language style. Two articles use formal style while one other article applies casual style. The writer concludes that formal style often appears in newspapers because of considering the discussion field and the target readers. Articles using the formal style provide the style that seems rigid with the dense sentence structure that is suitable according to the issue grabbed from the surroundings.